2022
DOI: 10.3390/jcm11102824
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Mycoplasma pneumoniae Pneumonia in Children: Early Recognition and Management

Abstract: Refractory Mycoplasma pneumoniae pneumonia (RMPP) is a severe state of M. pneumoniae infection that has attracted increasing universal attention in recent years. The pathogenesis of RMPP remains unknown, but the excessive host immune responses as well as macrolide resistance of M. pneumoniae might play important roles in the development of RMPP. To improve the prognosis of RMPP, it is mandatory to recognize RMPP in the early stages, and the detection of macrolide-resistant MP, clinical unresponsiveness to macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 152 publications
(215 reference statements)
1
36
0
2
Order By: Relevance
“…Refractory MPP (RMPP) is a condition that does not improve after seven days of standard Macrolide therapy ( 9 ). In recent years, the increasing proportion of RMPP has posed a significant challenge to paediatricians ( 10 ). A South Korean study of 5,294 children with pneumonia showed RMPP rates of more than 20% ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Refractory MPP (RMPP) is a condition that does not improve after seven days of standard Macrolide therapy ( 9 ). In recent years, the increasing proportion of RMPP has posed a significant challenge to paediatricians ( 10 ). A South Korean study of 5,294 children with pneumonia showed RMPP rates of more than 20% ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The airway and lung lesions of some individuals with refractory MPP (RMPP) remain severe, even if the children's body temperature returns to normal after standard treatment. Con dent children with RMPP suffer from problems, including atelectasis and pulmonary consolidation [14]. The bronchoscope has been widely used to diagnose and treat pediatric respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Kolejnym przykładem zastosowania genomiki porów nawczej we współczesnej nauce są badania nad Mycoplasma pneumoniae. Ta beztlenowa bakteria jest jedną z najczęstszych przyczyn infekcji górnych i dolnych dróg oddechowych oraz stanów zapalnych płuc, które rozwijają się u 10-40% zakażonych pacjentów [69]. Ze względu na niezdolność bakterii do syntezy peptydoglikanu, jest naturalnie oporna na antybiotyki β-laktamowe.…”
Section: Odwrotna Wakcynologia Pangenomowaunclassified